MACROPHYTES OF THE SAKHALIN SEA COAST (Makrofity Morskikh Poberezhii Sakhalina) - Vozzhinskaya,V. B. (1969)
The marine bottom flora of Sakhalin was studied. One hundred and sixty-five (165) species of the algae flora were observed; forty-seven (47) species are new to Sakhalin, and 5 species are new to science. Altogether there are 286 species of algae, 50 species belong to Chlorophyceae, 90 to Phaeophyceae, 146 to Rhodophyceae orders. Phytogeographically, the algae of Sakhalin are of different origin. A comparison of the algal flora of Sakhalin with other regions of the North Pacific shows that the algal flora of Sakhalin constitutes a phytogeographical boundary between the algal flora of the warm-water and cold-water regions of the North Pacific. The closest relationship exists between the algal flora of Sakhalin and Hokkaido. The vertical and horizontal distribution is diverse in supralitoral, litoral, upper sublitoral zone. This distribution depends on the bottom structure, the wave action, the height and mode of the tide. Only 75 species of all Skhalin algae are abundantly distributed. The distribution of biomasses varies from area to area. A number of algae can be used for food or for other purposes. Data on the distribution and crop of algae within Sakhalin are given in this study. (Author) Trans. of Akademiya Nauk SSSR. Institut Okeanologii. Trudy, v69 p330-441 1964, by M. Slessers.